Deformation and failure of PrintCast A356/316 L composites: Digital image correlation and finite element modeling. (October 2020) - Cheng, Jiahao; Gussev, Maxim; Allen, Jason; Hu, Xiaohua; Moustafa, Abdel R.; Splitter, Derek A.; Shyam, Amit
Abstract: A356/316 L interpenetrating phase composites can be fabricated by infiltrating additively-manufactured 316 L stainless-steel lattices with a molten A356 aluminum alloy, a new process termed PrintCasting. This work investigates the mechanical properties of PrintCast composites and their relation to the volume-fraction of 316 L reinforcement. Uniaxial tension experiments were conducted with A356/316 L PrintCast composites that had either 30 vol%, 40 vol% or 50 vol% 316 L. When 316 L reinforcement increased from 30 vol% to 40 vol%, a > 200% increase in ductility and 400% increase in absorbed-energy were observed, while a much lower increase was exhibited when reinforcement increased from 40 vol% to 50 vol%. The failure of the 30 vol% sample occurred by localized deformation and a single failure initiation region, in contrast to the 40 vol% and 50 vol% samples which failed by delocalized damage in the entire gauge section. To understand this transition phenomena, digital image correlation (DIC) was coupled with finite element (FE) analysis to capture the deformation and failure processes. The results revealed that, for all samples, stress concentrated and failure initiated in a 316 L strut near the lattice nodes, where the strut underwent localized bending-dominated deformation. In the high 316 L volume-fraction composites, the increase in 316 L-strut diameter reduced local bending stress and stabilized the deformation, leading to improved damage tolerance. Based on the presented analysis, local modifications to the PrintCast structure are suggested. Graphical abstract: Unlabelled Image Highlights: Combining directed energy based additive manufacturing with metal casting to create metallic constituent composites. Additively-manufactured 316 L lattices infiltrated with molten A356 Transition from localized deformation and fracture to delocalized damage with increase of 316 L Coupled digital image correlation and finite element analysis